Synchronization of Regulation and Path Dependence: The Main Challenge of UIN Jakarta's Transformation Towards Financial Independence - Riniwati (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
This policy paper analyzes the problem of the slow policy of accelerating the transformation of UIN Syarif Hidayatullah Jakarta from a Public Service Agency (BLU) to a State Religious Higher Education Institution with Legal Entity (PTKN BH), which is a crucial policy issue that threatens the fulfillment of the mandate of financial and academic independence. This paper aims to identify and analyze the structural root causes that hinder the optimization of business unit performance as the main prerequisite for PTN BH. Through Root Cause Analysis, three main obstacles were found: (1) Regulatory Rigidity and High Transaction Costs, caused by the attachment to the Government Goods/Services Procurement mechanism (Presidential Decree 16/2018) and overlapping regulations across ministries; (2) Weaknesses in Human Resource Governance, due to the Limited Competitive Salary and Incentive Structure under public personnel regulations; and (3) Social Mission Contradiction, namely the obligation to carry out PSO without adequate public budget compensation. The writing methodology used is Qualitative-Descriptive Policy Analysis. This approach involves an in-depth literature review of scientific papers (journals, theses, books) discussing New Public Management, Agency Theory, and PTN BH/BLU governance. Problem data is identified and mapped using USG Analysis (Urgency, Seriousness, Growth) to prioritize issues. Next, five policy alternatives are proposed and evaluated comparatively using William N. Dunn's Policy Evaluation Criteria (Effectiveness, Efficiency, Adequacy, Equity, and Responsiveness). The analysis results recommend the Spin-off Policy of Strategic Business Units into Legal Entity Subsidiaries (PT) as the most effective structural solution (highest score of 22). This recommendation ensures the termination of bureaucratic path dependence and allows business units to implement professional governance and remuneration, thereby accelerating the fulfillment of financial health requirements towards PTKN BH status.